2016
DOI: 10.1186/s12984-016-0150-9
|View full text |Cite
|
Sign up to set email alerts
|

A biologically-inspired multi-joint soft exosuit that can reduce the energy cost of loaded walking

Abstract: BackgroundCarrying load alters normal walking, imposes additional stress to the musculoskeletal system, and results in an increase in energy consumption and a consequent earlier onset of fatigue. This phenomenon is largely due to increased work requirements in lower extremity joints, in turn requiring higher muscle activation. The aim of this work was to assess the biomechanical and physiological effects of a multi-joint soft exosuit that applies assistive torques to the biological hip and ankle joints during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
189
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 258 publications
(205 citation statements)
references
References 45 publications
(51 reference statements)
5
189
2
1
Order By: Relevance
“…Our first efforts developing exosuits led to the creation of systems that could comfortably deliver assistive forces to healthy users during walking (39,40,(43)(44)(45)(46)(47). Recently, we demonstrated that assistive forces delivered through the exosuit interface produce marked reductions in the energy cost of healthy walking (37,48). Thus, although exosuits can only augment, not replace, a wearer's existing gait functions, we posit that they have the potential to work synergistically with the residual abilities of individuals with impaired gait to improve walking function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our first efforts developing exosuits led to the creation of systems that could comfortably deliver assistive forces to healthy users during walking (39,40,(43)(44)(45)(46)(47). Recently, we demonstrated that assistive forces delivered through the exosuit interface produce marked reductions in the energy cost of healthy walking (37,48). Thus, although exosuits can only augment, not replace, a wearer's existing gait functions, we posit that they have the potential to work synergistically with the residual abilities of individuals with impaired gait to improve walking function.…”
Section: Introductionmentioning
confidence: 99%
“…To address this opportunity, our team developed a lightweight, soft wearable robot (exosuit) that interfaces to the paretic limb of persons after stroke via garment-like, functional textile anchors. Exosuits produce gait-restorative joint torques by transmitting mechanical power from waist-mounted body-worn (37) or off-board (38,39) actuators to the wearer through the interaction of the textile anchors and a cable-based transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the requirements on the accuracy and consistency of a cable force controller for such devices can be relatively lax compared with the requirements for upper limb devices. For example, an invariant trapezoidal force profile triggered once per gait cycle has been found sufficient to reduce metabolic costs during walking [18].…”
Section: Design Factorsmentioning
confidence: 99%
“…The effectiveness of each prototype is commonly assessed by measuring the metabolic cost reduction delivered to the user while performing an activity [1]. However, the latter requires specialized equipment.…”
Section: Introductionmentioning
confidence: 99%